80.1k views
5 votes
Solve for t.
-3t + 3 – 7t = -90 – 7

User Atorian
by
4.4k points

2 Answers

4 votes

Answer:

Explanation:

-3t + 3 - 7t = -90 - 7

-10t + 3 = -97

-10t = -100

t = 10

User Judehall
by
5.0k points
6 votes

Answer:

t = 10

Explanation:

-3t + 3 - 7t = -90 - 7

Simplify both sides of the equation

That's

- 10t + 3 = - 97

Using the subtraction property subtract 3 from both sides of the equation

We have

- 10t + 3 - 3 = -97 - 3

- 10t = - 100

Divide both sides by - 10


( - 10t)/( - 10) = ( - 100)/( - 10)

We have the final answer as

t = 10

Hope this helps you

User Jzonthemtn
by
5.2k points